Integrating Digital Capability and Psychological Hardiness to Foster Sustainable Entrepreneurial Intention: Evidence from a Cross-National Indonesia–Malaysia Study - Akhmad Darmawan; Fatmah Bagis; Suyoto; Ahmad Zainal bin Abd Razak (Attractive : Innovative Education Journal, 2025)
The rapid diffusion of digital technologies and the imperative of sustainable economic development converge to place unprecedented demands on aspiring entrepreneurs. The cognitive and psychological pathways through which individuals translate technological competence and psychological hardiness into a firm commitment to sustainable venturing remain underexplored, particularly in cross-national ASEAN settings. This study examines how digital capability and psychological hardiness jointly shape sustainable entrepreneurial intention, with hardipreneurial self-efficacy as mediator and institutional support as moderator. Grounded in Social Cognitive Theory (Bandura, 1997; 2023) and applying PLS-SEM on N = 300 students across Indonesia and Malaysia, the findings confirm all six hypotheses. Digital capability and psychological hardiness each significantly influence hardipreneurial self-efficacy, which fully mediates both pathways to sustainable entrepreneurial intention, while institutional support significantly amplifies the efficacy–intention link. These findings advance sustainable entrepreneurship theory and generate actionable policy implications for university ecosystems and SDG-aligned entrepreneurship programs in ASEAN.